Training of Motion Control May Not Improve Tool-Manipulation Ability in Rats (Rattus norvegicus) - Nagano, Akane (Frontiers in Psychology, 2022)
In recent times, previous studies have reported the manipulation of tools by rats (Nagano, 2019a, 2019b, 2021; Nagano and Aoyama, 2017a, 2017b) and degus (Kumazawa-Manita et al., 2013; Okanoya et al., 2008) in controlled experimental settings. However, Nagano (2021) reported that only one out of eight experimentally naïve rats could manipulate a rake-shaped tool according to the position of a food reward without prior experience of obtaining the reward with the tool before the test. The present study aimed to improve the training of rats and investigate rodents’ ability to manipulate tools according to food position. Stricter criteria were employed when training the rats to promote the rats’ monitoring of their own tool manipulation. Additional training was introduced to give them the opportunity to learn that the reward moved closer to them by pulling an object connected to the reward. The present study showed that only one of eight rats could manipulate a tool according to the position of the reward without prior experience of obtaining the reward with the tool or perceiving that part of the tool came in contact with the reward, as the previous study showed. The change in training did not enhance the rats’ tool-manipulation ability according to the food position. These procedures should be conducted in a wider variety of animals to investigate whether the training in motion control can promote the subjects’ effective tool-use behavior.